2020
DOI: 10.1128/aac.01816-19
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime-Avibactam Resistance Associated with Increased bla KPC-3 Gene Copy Number Mediated by pKpQIL Plasmid Derivatives in Sequence Type 258 Klebsiella pneumoniae

Abstract: This study reports on the characterization of two ceftazidime-avibactam (CZA)-resistant KPC-producing Klebsiella pneumoniae strains (KP-14159 and KP-8788) sequentially isolated from infections occurred in a patient never treated with CZA. Whole-genome sequencing characterization using a combined short- and long-read sequencing approach showed that both isolates belonged to the same ST258 strain, had altered outer membrane porins (a truncated OmpK35 and an Asp137Thr138 duplication in the L3 loop of OmpK36), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 32 publications
7
30
1
Order By: Relevance
“…The results were consistent with some previously published studies (Shen et al, 2017;Zhang et al, 2020). The higher copy numbers of bla KPC−2 may potentially result from the high copy numbers of the plasmids carrying bla KPC (Roth et al, 2011) and/or a duplication of mobile genetic elements associated with bla KPC (Coppi et al, 2020). Since the examination of the bla KPC−2 promoter regions failed to identify any mutations, the higher bla KPC gene expression may potentially be affected by the higher copy numbers of bla KPC or other gene regulatory mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…The results were consistent with some previously published studies (Shen et al, 2017;Zhang et al, 2020). The higher copy numbers of bla KPC−2 may potentially result from the high copy numbers of the plasmids carrying bla KPC (Roth et al, 2011) and/or a duplication of mobile genetic elements associated with bla KPC (Coppi et al, 2020). Since the examination of the bla KPC−2 promoter regions failed to identify any mutations, the higher bla KPC gene expression may potentially be affected by the higher copy numbers of bla KPC or other gene regulatory mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…Intriguingly, in addition to the high level of carbapenem resistance with a meropenem MIC of 1,024 mg/L, strain KP3034 exhibited a higher MIC level for CAZ/AVI (16/4 mg/L) than the other strains detected. In contrast to the alteration recently reported by Coppi et al 26 two-amino-acid duplications (Gly136-Asp137) within transmembrane β-strand loop 3 (L3) of OmpK36 were observed in KP3034, which was previously associated with reduced susceptibility to carbapenems. 27 Since there is no history of previous antimicrobial exposure to CAZ/AVI treatment or specific mutations were observed in the bla KPC-2 gene, hyperexpression of the bla KPC-2 gene associated with alteration in the outer membrane or other unknown mechanisms might account for this low level of CAZ/AVI resistance.…”
Section: Discussioncontrasting
confidence: 76%
“…It was reasonable to assume that there was a correlation between the bla KPC-2 copy number and CAZ-AVI resistance. Previous studies had demonstrated β-lactamase gene amplification correlated with the susceptibility to β-lactam/β-lactamase inhibitor combination agents [54-56]. Our results supported these conclusions.…”
Section: Discussionsupporting
confidence: 90%